2011
DOI: 10.1111/j.1365-2141.2011.08820.x
|View full text |Cite
|
Sign up to set email alerts
|

VcR‐CVAD induction chemotherapy followed by maintenance rituximab in mantle cell lymphoma: a Wisconsin Oncology Network study

Abstract: Intensive chemotherapy regimens are not feasible in many adults with mantle cell lymphoma (MCL). We sought to build upon our previous experience with a non-intensive regimen, modified R-hyperCVAD chemotherapy (rituximab, cyclophosphamide, vincristine, doxorubicin, dexamethasone) with maintenance rituximab (MR), by the incorporation of bortezomib (VcR-CVAD) and the extension of MR beyond 2 years. Patients with previously untreated MCL received VcR-CVAD chemotherapy every 21 days for 6 cycles. Patients achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 33 publications
(43 reference statements)
0
45
1
Order By: Relevance
“…Importantly, we did not observe excessive painful peripheral neuropathy using the dose and schedule of vincristine and bortezomib selected for this trial. 13 Nearly 90% of patients were able to complete all 6 cycles of induction therapy, compared with just 61% who were able to complete conventional R-hyperCVAD with alternating R-methotrexate and cytarabine in a SWOG study. 25 The CR rate of 68% is encouraging and possibly an underestimate of the true CR rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, we did not observe excessive painful peripheral neuropathy using the dose and schedule of vincristine and bortezomib selected for this trial. 13 Nearly 90% of patients were able to complete all 6 cycles of induction therapy, compared with just 61% who were able to complete conventional R-hyperCVAD with alternating R-methotrexate and cytarabine in a SWOG study. 25 The CR rate of 68% is encouraging and possibly an underestimate of the true CR rate.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] In this pilot trial of 30 patients, median age 61, VcR-CVAD with MR demonstrated a CR rate of 77%, an OR rate of 90%, and 3-year PFS and OS of 63% and 86%, respectively. 13 These results were considered promising and worthy of additional study. Of note, 7 of the first 14 patients enrolled experienced painful peripheral neuropathy when bortezomib at 1.5 mg/m 2 was administered in combination with vincristine at 2 mg. With dose modification of both agents (vincristine 1 mg on day 3, bortezomib 1.3 mg/m 2 on days 1 and 4), only 1 in 16 final patients enrolled experienced painful peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In previously untreated patients with MCL, bortezomib plus R-CHOP resulted in an ORR of 81%, CR of 64%, and PR of 17%, with median PFS of 23 months and median OS not reached at median follow-up of 34 months (106). Another study that incorporated bortezomib into modified R-hyperCVAD in untreated patients with MCL resulted in an ORR of 90%, CR of 77%, and PR of 13%, with 3-year PFS and OS of 63% and 86%, respectively (107).…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…42), leading to extended FDA approval for bortezomib in previously untreated MCL in October 2014 (43). Because of hyper-CVAD-related toxicity (44), a modified combination (no cytarabine or methotrexate) was developed with results intermediate between R-CHOP and standard hyper-CVAD, but better tolerated, also offering a platform for bortezomib combinations (45). This benefit was confirmed in the multicenter setting by the ECOG E1405 study, in which VcR-CVAD followed by maintenance rituximab in newly diagnosed MCL showed an ORR of 95%, with a 68% CR/CR unconfirmed (CRu), and 3-year PFS of 72% (46).…”
Section: R-chop-like Inductionmentioning
confidence: 99%